Coverage Evaluation and Compliance of Mass Drug Administration Campaign in Nanded District of Maharashtra - Khan, Nazia Aram M; Gattani, Prakash L; Inamdar, Ismail A; Domple, Vijay K; Nina, Madhukar B (National Journal of Community Medicine, 2017)
Background: Lymphatic filariasis (LF) is endemic in 83 countries and territories. In view with the global elimination, mass drug administration (MDA) with single dose of diethyl carbamazine and albendazole tablets was carried out for the eligible population in Nanded district. The study was conducted to assess coverage, compliance and reasons for noncompliance to MDA in Nanded district. Method: A community-based cross-sectional study was done by house-to-house visit in Nanded district. Three rural and one urban clusters of Nanded district, Maharashtra, were selected. A predesigned questionnaire was used to collect information. Drug coverage, compliance, effective coverage, coverage–compliance gap (CCG), reasons for noncompliance were studied. Statistical analysis was done by SPSS version 16. Results: The total numbers of houses surveyed were 120. Coverage rate was 94.40%, and compliance rate, CCG, effective coverage rate was 51.81%, 8.48%, and 48.91%, respectively. The compliance of drugs by eligible population was slightly higher in urban area (95.41%) than the rural area (90.56%). Major reasons for non consumption of drug were empty stomach during Drug distributor (DD) visit. Conclusion: The drug compliance need to be improved. Issues like fear of side effects should be addressed through effective behavior change communication strategies.